The effects of website design elements on the customer experience in fast-fashion online shopping - Santos, Carolina Andrade (2021)
In an era in which online shopping is becoming increasingly important, companies’ success depends on the ability to include website design elements on products’ webpages to evoke effective customer experiences. These elements provide not only information but also entertainment, mimic sensory experiences and human interactions from the offline world. Based on past literature investigation, an online survey, four customer interviews, and a sense-check expert interview, the author approaches how can companies use the different website design elements (descriptive detail, bulleted features, product image, lifestyle product image, zoom picture, product video, customer reviews, recommendation algorithm, content filters, chatbots, chatlines, smart fitting technology, return policy and shipping information) to build powerful online customer experiences (informativeness, entertainment, sensory appeal, and social presence) in shopping for fast-fashion clothing brands for Portuguese consumers. The findings offer significant theoretical contributions and actionable managerial implications to customer experience. Firstly, companies should focus on informativeness and entertainment, followed by sensory appeal and social presence. In order to build informativeness experiences, companies need to focus on descriptive detail, product images, lifestyle product images, zoom images, customer reviews, and recommendation algorithms. The lifestyle product image, zoom image, product video, customer reviews, recommendation algorithm, and content filters build entertainment experiences. For the sensory appeal experience, companies should use product images, zoom pictures, and product video. Moreover, descriptive detail, product image, recommendation algorithm, chatbots, chatlines, smart fitting technology, and return policy information should be presented for social presence.